Information and Communication Technology in a Global World - Christer Lars Ohlin (Research in Social Sciences and Technology, 2019)
This study takes its departure from ongoing debate about teachers’ (collective) “continuing professional development” (CPD). The overall aim is to highlight active teachers’ perceptions on developing a self-understanding of their complex role in daily practice by using digital tools. The following research questions guided the study: How can teachers make schools more relevant and engaging? How can students’ achievement increase? In what way can teachers provide high-quality education for all students? Three perspectives will be guiding the study: Information and Communication Technology (ICT), learning, and special education. The participants in the study are 21 staff members in preschool, primary school, and a recreation center with whom we conducted structured individual interviews and focus group discussions. Field notes were also taken during the interview and discussion sessions. The findings reveal the importance of the teachers’ deeper understanding of students’ creativity, critical thinking, communication, and collaboration. Furthermore, the most powerful thing teachers can do is to design engaging, meaningful, and authentic work and technology-enhanced learning experiences. In order to improve learning in a digital world, the teachers must be engaged and supported by professional learning opportunities to continually improve and strengthen their digital competencies and teaching practices. The theoretical standpoint is the norm model as an analytical tool to understand the teachers’ perceptions. The concept of “norm” is a collective term for the factors and structures that are regarded as a normal balance between the aspects of value/will, system conditions/possibilities, and cognition/knowledge.